Relationship between staple food types and cardiovascular disease risk among older Chinese adults - Chen, Chunmei; Zhao, Fayun; Du, Maozong; Wang, Xin (Frontiers in Nutrition, 2025)
BackgroundDietary habits, particularly staple food consumption, play a significant role in influencing cardiovascular disease (CVD) risk. However, limited research has examined the relationship between staple food types and CVD incidence in aging populations, especially in China. This study aims to identify which types of staple foods are most beneficial for cardiovascular health among older Chinese adults.MethodsData from the Chinese Longitudinal Healthy Longevity Survey (CLHLS) were analyzed to explore the associations between staple food types (rice, wheat, and coarse cereals) and CVD risk among 16,498 adults aged 65 and older. Cox proportional hazards models were employed to evaluate the relationship between staple food types and CVD incidence, while restricted cubic splines assessed potential non-linear relationships between staple food intake and CVD risk. Stratified analyses were performed based on age, sex, and hypertension history.ResultsDuring a median follow-up of 7.38 years, 1757 participants experienced new-onset CVD. Wheat as a staple food was related to a 40.8% higher risk of CVD compared to rice (HR: 1.408; 95% CI: 1.195–1.658; p < 0.001), while no significant association was observed for coarse cereals. Stratified analyses revealed that the association with wheat was stronger among participants aged 65–79 years, males, and those without hypertension. No linear relationship was found between intake levels of rice, wheat, or coarse cereals and CVD risk, but non-linear associations emerged for rice and wheat intake (P for non-linear association<0.001 and = 0.010, respectively). A U-shaped relationship was observed for wheat, with the lowest CVD risk at a cooked intake of 375 g/day, consistent with dietary guidelines.ConclusionThis study highlights the differential impact of staple food types on CVD risk, with wheat consumption linked to a higher incidence of CVD compared to rice, particularly in specific subgroups. These findings provide evidence to inform dietary guidelines for older Chinese adults and underscore the need for further research into the underlying mechanisms.